Analysis on Behavioral Intention of Financial Auditors in Adopting Big Data Analytics - Mulyawan, Archie Nathanael; Deniswara, Kevin; Setiadi, Rudy (Bina Nusantara University, 2024)
The rapid development of technology brings significant changes to all business activities, where auditors need to collaborate with IT. A financial auditor's ability to adopt the system is caused by several factors that encourage greater audit competence, where in-depth analysis is needed to identify all these factors, so this research aims to analyse financial auditors in adopting Big Data Analytics in financial report audits with the UTAUT Model. This research uses an explanatory quantitative method by gathering 70 auditors from public accounting firms in the Jakarta area by adopting SEM-PLS which was processed with SmartPls ver3. The results found all variables have a positive effect on behavioural intention. However, the relationship is not moderated by gender and Audit firm size. Thus, it is known that large and small Audit firm size have already adopted big data analytics, where the advances of companies require auditors to be able to practice. Therefore, it is necessary to analyst the potential of auditors to improve audit quality. Keywords: Big data analytics, Financial auditors, UTAUT model, Audit quality